2014
DOI: 10.1142/s0192415x1450092x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Anti-Gout Activity of Chlorogenic Acid: Improvement on Hyperuricemia and Gouty Inflammation

Abstract: Gout is a metabolic disorder associated with hyperuricemia resulting in the deposition of monosodium urate (MSU) crystals in joints and tissues. Lowering serum uric acid (Sur) levels and anti-inflammation are highly essential in treating gout. Chlorogenic acid (CA), as one of the most abundant polyphenols in the Chinese medicines, has been rarely reported to have an anti-gout effect. The model of potassium oxonate (PO)-induced hyperuricemia in mice and MSU crystal-induced inflammation in rats has been establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Among these compounds, chlorogenic acid [13], 3,5-dicaffeoylquinic acid [11], 4,5-dicaffeoylquinic acid methyl ester [10] and 1,5-dicaffeoylquinic acid [12] showed significant inhibition of xanthine oxidase activity and anti-hyperuricemia. Thus, anti-hyperuricemia effects by uricosuric or inhibition of xanthine oxidase way by the G. pensylvanicum extracts can be partially attributed to caffeoylquinic acid derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these compounds, chlorogenic acid [13], 3,5-dicaffeoylquinic acid [11], 4,5-dicaffeoylquinic acid methyl ester [10] and 1,5-dicaffeoylquinic acid [12] showed significant inhibition of xanthine oxidase activity and anti-hyperuricemia. Thus, anti-hyperuricemia effects by uricosuric or inhibition of xanthine oxidase way by the G. pensylvanicum extracts can be partially attributed to caffeoylquinic acid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that G. pensylvanicum extract (GPE) possess many caffeoylquinic acid derivatives and showed potent inhibitory activity against XO in vitro. Meanwhile, caffeoylquinic acid derivatives had been report that they showed potential anti-huperuricemia and anti-gouty arthritis effect [1013]. In addition, previous pharmacology works on various species of the Gnaphalium genus and its components possess XO inhibitory activity, showed significantly anti-hyperuricemia and anti-gouty arthritis [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is clinically desirable to combine a compound with allopurinol therapy to potentiate the effects of allopurinol and to reduce the required high doses of the drug for better treatment safety [6,15]. Some natural products have been effective in hyperuricemic control and gout treatment [16][17][18]. Smilax riparia A. DC, belonging to the genus Smilax in the family Liliaceae, is a botanical widely grown in the southern and central parts of China.…”
Section: Introductionmentioning
confidence: 99%
“…It regulates various biological processes and has anti-inflammatory [21], anti-diabetic [22], anti-tumorigenic [23], antioxidative [24], anti-gout [25], and anti-obesity [26] effects. Recently, it has been shown that CA inhibits HIF-1α mRNA expression [27] and angiogenesis through the AKT pathway [28].…”
Section: Introductionmentioning
confidence: 99%